Heterogeneity of the alpha subunit of tubulin and the variability of tubulin within a single organism (The Rockefeller University Press, 1976)
When tubulins obtained from particular microtubules of the sea urchin (ciliary doublet A tubules, flagellar doublet microtubules, and mitotic microtubules) are analyzed by electrophoresis in a polyacrylamide gel system containing sodium dodecyl sulfate and urea, heterogeneity of the alpha subunit, and differences between the tubulins are revealed. The alpha subunit of tubulin from mitotic apparatus and from A microtubules of ciliary doublets is resolved into two bands, while the alpha subunit of flagellar doublet tubulin gives a single band. The mitotic and ciliary tubulins differ in the mobilities of their two alpha species, or in the relative amounts present, or both. The existence of differences between the tubulins has been confirmed by a preliminary analysis of their cyanogen bromide peptides.